2020
DOI: 10.1111/head.13738
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Controlled Trial to Assess the Impact of Motivational Interviewing on Initiating Behavioral Therapy for Migraine

Abstract: Background.-Relaxation, biofeedback, and cognitive behavioral therapy are evidence-based behavioral therapies for migraine. Despite such efficacy, research shows that only about half of patients initiate behavioral therapy recommended by their headache specialists.Objective.-Motivational interviewing (MI) is a widely used method to help patients explore and overcome ambivalence to enact positive life changes. We tested the hypothesis that telephone-based MI would improve initiation, scheduling, and attending b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Furthermore, when referred for conventional in-person behavioral therapy for migraine, prior studies show that many people with migraine do not follow-up with the recommended intervention. 14,15 Participants have cited lack of accessibility (cost and time) as being the barrier to treatment. 15 Thus, the RELAXaHEAD intervention with PMR that people can do on their own without paying a provider is a potential solution for some patients to access care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, when referred for conventional in-person behavioral therapy for migraine, prior studies show that many people with migraine do not follow-up with the recommended intervention. 14,15 Participants have cited lack of accessibility (cost and time) as being the barrier to treatment. 15 Thus, the RELAXaHEAD intervention with PMR that people can do on their own without paying a provider is a potential solution for some patients to access care.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13 Furthermore, even when people are referred for behavioral therapy for migraine, few people attend the behavioral therapy appointments. 14,15 Time and cost are frequently cited by patients as barriers to pursuing behavioral therapy for migraine. 14,15 Effective, accessible, nonpharmacologic, prevention management strategies are needed to improve migraine management in the primary care setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we examined: (a) lack of knowledge regarding non-pharmacological treatment options among referring practitioners and headache patients; (b) the relatively limited number and distribution of clinicians trained in non-pharmacological headache treatments; (c) demographic-minority, socio-economic, and third-party payerrelated disparities in healthcare access; and (d) societal stigma associated with a diagnosis of headache, compounded by the stigma of referral to a perceived "psychiatric" treatment. We also present barriers identified by our team of experts (based on experiences and prior publications) [13][14][15][16][17] for both healthcare providers and patients, along with ways to overcome these barriers (Table 1). Using the Transtheoretical Model of Stages of Change, 18 we show how healthcare providers and patients may advance from one stage to the next to overcome barriers (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…Time was cited as the most common barrier to initiating the behavioral therapy 5 . A randomized controlled study found that motivational interviewing increased the rates of inquiring about the behavioral therapy but not the rates of scheduling or attending therapy appointments 6 . Apprehension about the time commitment, cost, and difficulty accessing the treatment were cited as some of the barriers to scheduling/attending these appointments.…”
Section: Introductionmentioning
confidence: 99%